PERAN DINAS PEMUDA OLAHRAGA KEBUDAYAAN DAN PARIWISATA TERHADAP PEMBINAAN OLAHRAGA PADA PENYANDANG DISABILITAS - Zahra, Zahra Citra Fanita; Fajar, Fajar Awang Irawan; Azyumardi, Azyumardi Azra (Journal of Sport and Exercise Science, 2023)
This study aims to determine the role played by the Department of Youth, Sports, Culture and Tourism (Disporyata) in fostering sports achievements for persons with disabilities in Depok City. The type of research used in this research is quantitative descriptive with purposive sampling technique. Checking the validity of the research data using source triangulation and technical triangulation. The data analysis technique in this study uses statistical data through quantitative descriptive with the percentage of data from surveys, data collection uses closed statements, namely questionnaires. Respondents in this study amounted to 40 respondents consisting of members of the Disporata, Depok City NPC administrators, and athletes with disabilities. The results of this study found that the role of Disporyata in sports coaching for persons with disabilities was not optimal because there were still many inadequate facilities and infrastructure in the field. The city government pays less attention to sports achievements for people with disabilities, and the sports awards given are deemed inappropriate for athletes with disabilities. Attention from the city government to the development of sports achievement for persons with disabilities needs to be more intensive. The limitations in this study are openness and honesty in providing information in filling out questionnaires and the research is still not in-depth, so that further research is expected to respond to respondents in more detail and actual information in accordance with the conditions in the field.